2019
DOI: 10.1002/ece3.5474
|View full text |Cite
|
Sign up to set email alerts
|

Global genetic diversity, lineage distribution, and Wolbachia infection of the alfalfa weevil Hypera postica (Coleoptera: Curculionidae)

Abstract: The alfalfa weevil (Hypera postica) is a well‐known example of a worldwide‐distributed pest with high genetic variation. Based on the mitochondrial genes, the alfalfa weevil clusters into two main mitochondrial lineages. However, there is no clear picture of the global diversity and distribution of these lineages; neither the drivers of its diversification are known. However, it appears likely that historic demographic events including founder effects played a role. In addition, Wolbachia, a widespread intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 121 publications
(129 reference statements)
3
9
0
Order By: Relevance
“…The Western clade individuals in northern France, the Netherlands, the Czech Republic, and Poland were infected with Wolbachia (Fig. 2 ), and all of them had identical ftsZ (699 bp), coxA (432 bp), and hcpA (463 bp) sequences as reported previously 46 , which corresponds to the prevailing strain wHypera1 47 . In contrast, Western clade individuals found in coastal southern France, Spain, Latvia, Hungary, and Croatia were uninfected (Fig.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The Western clade individuals in northern France, the Netherlands, the Czech Republic, and Poland were infected with Wolbachia (Fig. 2 ), and all of them had identical ftsZ (699 bp), coxA (432 bp), and hcpA (463 bp) sequences as reported previously 46 , which corresponds to the prevailing strain wHypera1 47 . In contrast, Western clade individuals found in coastal southern France, Spain, Latvia, Hungary, and Croatia were uninfected (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Hypera postica ( n = 149) were obtained from 33 localities covering most of its native distribution range (Table 1 ). Adults were collected from cultivated and wild legume vegetation of Medicago 47 , Trifolium in Egypt, and Vicia cracca in Bulgaria, mostly during the latest decade. The samples were then stored in ethanol at 4 °C until DNA extraction .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several host‐shift events among closely related species, as inferred from patterns of Wolbachia strain distributions on host phylogenies, support the PDE hypothesis, e.g. in weevils (Lachowska, Kajtoch, & Knutelski, 2010; Sanaei et al ., 2019), Trissolcus wasps (Guz et al ., 2012), and Drosophila (Haine, Pickup, & Cook, 2005; Turelli et al ., 2018). By contrast, in some case studies focused on certain arthropod families or genera, only a negligible part of the data, if any, appeared to indicate a PDE, e.g.…”
Section: Factors Influencing Host Shiftsmentioning
confidence: 99%
“…Most of the studies regarding the temperature-dependent development of H. postica have been focused in larvae and pupae and have been carried out with populations from North America and Middle East Asia [ 14 , 18 ]. The results of these studies suggested wide variations in geographical regions [ 19 , 20 , 21 ]. On the other hand, literature dealing with the effect of abiotic factors on embryonic development is scarce.…”
Section: Introductionmentioning
confidence: 99%